Epidemiologic burden of hospitalisation for congestive heart failure among adults aged ≥19 years in the Philippines. Issue 1 (27th March 2017) - Tumanan-Mendoza, Bernadette A; Mendoza, Victor L; Bermudez–Delos Santos, April Ann A; Punzalan, Felix Eduardo R; Pestaño, Noemi S; Natividad, Rudy Boy; Shiu, Louie Alfred; Macabeo, Renelene
Abstract : Objectives: The study determined the prevalence of hospitalisation due to congestive heart failure (CHF) among adult patients aged 19 years and above in the Philippines and its 17 regions in 2014. It also determined the demographic profile of these patients, aetiology and type of CHF, comorbidities, duration of hospitalisation and the overall in-hospital mortality rate. Methods: Data collection was done using the hospitalisation claims database of the Philippine Health Insurance Corporation (PhilHealth). All patient claims for CHF, that is, patients who were admitted from 1 January to 31 December 2014, were included. Descriptive statistics were utilised to obtain the results. Results: The prevalence rate was 1.6% or 1648 cases of CHF for every 100 000 patient claims for medical conditions in 2014. The mean age was 52.6±15.1 years. There was no sex predilection. Only 22.67% of the hospitalisation claims for CHF listed possible specific aetiologies, the most common of which was hypertensive heart disease (86.7%). There were more cases of systolic compared to diastolic heart failure. The mean length of hospital stay was 5.9 days (+8.2) days (median 4 days), with an overall in-hospital mortality rate of 8.2%. Conclusions: There were 16 cases of heart failure for every 1000 Filipino patients admitted due to a medical condition in 2014. Hypertension was possibly the most common aetiologic factor. Compared to western and Asia-Pacific countries, the local mortality rate was relatively higher.